Wolf trap : a thriller - Sullivan, Connor (Emily Bestler Books/Atria, 2023)
A former Ground Branch paramilitary officer, Brian Rhome, thinking his time with this elite group of shadow operatives was over, instead finds himself in the midst of a deadly conspiracy that threatens the highest levels of American democracy.